2018
DOI: 10.3390/app8112304
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Steel Bar Corrosion Monitoring Using a Piezoceramic Transducer Enabled Time Reversal Method

Abstract: Steel bars, which are commonly used as reinforcements in concrete structures, are slender rods and are good conduits for stress wave propagation. In this paper, a lead zirconate titanate (PZT)-based steel bar corrosion monitoring approach was proposed. Two PZT transducers are surface-bonded on the two ends of a steel rod, respectively. One works as actuator to generate stress waves, and the other functions as a sensor to detect the propagated stress waves. Time reverse technology was applied in this research t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 72 publications
(79 reference statements)
0
50
0
Order By: Relevance
“…Past researches have shown that the wavelet package-based energy is sensitive to cracks in concrete structures [62,63]. When the stress wave propagates inside the prestressed curved tendon duct, due to the duct grouting defects, reflection attenuation [64,65], scattering attenuation, and absorption attenuation of stress wave will result in a large loss of stress wave energy. Therefore, the defect degree of the curved tendon duct can be judged according to the change of energy.…”
Section: Wavelet Packet-based Energy Methodsmentioning
confidence: 99%
“…Past researches have shown that the wavelet package-based energy is sensitive to cracks in concrete structures [62,63]. When the stress wave propagates inside the prestressed curved tendon duct, due to the duct grouting defects, reflection attenuation [64,65], scattering attenuation, and absorption attenuation of stress wave will result in a large loss of stress wave energy. Therefore, the defect degree of the curved tendon duct can be judged according to the change of energy.…”
Section: Wavelet Packet-based Energy Methodsmentioning
confidence: 99%
“…Steel structures of various forms are widely used in constructions [1,2], however, with adverse factors such as corrosion [3,4], dynamic loads [5,6], and impacts [7,8], steel structures are subject to damages [9,10]. Carbon fiber reinforced polymer (CFRP) materials are widely used to retrofit or reinforce damaged steel structures [11][12][13] due to their high strength-to-weight ratio, excellent corrosion resistance, and fast and easy installation.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies on debonding detection between a CFRP plate and steel beam using active sensing have been reported. In addition, the PZT-enabled active sensing methods often require the permanent installation of the transducers on or in the host structures [4,34,38,42,47,48], which brings inconvenience to large-scale implementation. These factors motivate the authors to develop a new approach to detecting debonding between steel structures and the reinforcing CFRP plates.…”
Section: Introductionmentioning
confidence: 99%
“…The NPW method often employs pressure sensors or other types of sensors that can detect wave propagation. Thanks to the recent development in structural health monitoring [19][20][21][22][23][24][25][26] and damage detection [27][28][29][30][31][32][33], many new types of sensors, such as piezoceramic transducers [34][35][36][37][38][39] and fiber optic sensors [40][41][42][43], have been developed for civil infrastructure. Because of their high bandwidth and low cost, piezoceramic transducers have…”
Section: Introductionmentioning
confidence: 99%